THE ANALYSIS OF STUDENTS’ CREATIVE THINKING ABILITY USING MIND MAP IN BIOTECHNOLOGY COURSE (Program Studi Pendidikan IPA Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA), 2016)
Process of learning which generally practiced nowadays is mostly in the form of face-to-face (lecturing) and one way communication. Sometimes the students are given tasks to fulfill the material target in one semester such as papers, internet-based summary, and/or other articles. Such things cause learners accustomed to convergent thinking and not to divergent thinking. Mind map is one of creative products which conducted by learners in learning process. Learning with mind map focuses more on the activeness and creative activity of the students. It will improve their ability to memorize and strengthen concept understanding of the student, and improve their creative thinking ability. This research was focused to analysis the creative thinking skills students using mind mapping in biotechnology course. The participant was students of Biology Education (N=55) consisting of two team that was team A (N=25) and team B (N=30). The result showed gain value of each team of creative thinking skills which were: team A (0.62) with three category: low (8%), average (40%), and high (52%). Team B (0,04) with three category: low (80%), average (10%) and high (10%).